Residual stress and distortiondistribution in butt welded joint of two aisi 304 stainless steel plates - Hoàng Trọng Ánh; Nguyễn Hồng Thanh; Hà Xuân Hùng; Nguyễn Tiến Dương (Journal of Technical Education Science, 2018)
Stainless steel is a type of material widely used in manufacturing structural steel, machinery,corrosion and temperature resistant pipes and tanks, etc.This paper uses finite element method to analyse and predict the distribution of residual stress and distortionof the butt welded joint between two AISI 304 stainless steel plates. When two plates are joined by welding, a complex thermal cycle is applied to the weldment. Thermal energy applied results in irreversible elastic-plastic deformation and consequently gives rise to the residual stresses in and around fusion zone and heat affected zone (HAZ). The prediction about welding residual stress and distortion is an important task when designing welded structure. Furthermore, this investigation provides a proper butt welding sequence to reduce costs, improve workability and increase fabrication capabilities of the welded structure.